Juventudes e agroecologia: cultivando espaços e práticas de agricultura na Região Metropolitana de Belo Horizonte - Ghiulia Cabral Martins (2023)
In recent years, youth have expanded their political participation in the national agroecological movement, resulting in the formation of groups and collectives seeking pathways towards more just and sustainable territories. In the Metropolitan Region of Belo Horizonte (RMBH), we can find initiatives marked by youth protagonism that point to agroecology as a transformative, pedagogical, and mobilizing tool. In this context, the present study investigates these experiences and their territorial, social, and educational implications, aiming to discuss to what extent their actions promote the production and transformation of space, social exchanges, and the construction and exchange of knowledge. The methodology used was empirical research, with data collection in the field and through questionnaires, analyzed through a qualitative approach supported by literature review. The geographical scope of the study is limited to RMBH. The work is presented in three main stages: theoretical survey (Chapter I), mapping/characterization of experiences (Chapter II), and reflections-dialogues based on the addressed experiences (Chapter III). It is concluded that strengthening youth in the agroecological movement is essential to promote significant changes towards a more sustainable and equitable future, where agricultural and food practices are guided by values of respect for nature, social justice, and active youth participation. Furthermore, relevant challenges were identified, such as the need to strengthen specific public policies, encourage mobilization and preparation of more young people for agroecological initiatives, and promote integration and articulation between urban and rural agroecological movements and experiences. Finally, the importance of promoting public debate on the subject is emphasized to strengthen and give visibility to youth agroecological movements, fostering sustainable and just practices for the development of counter-hegemonic, equitable, and environmentally responsible ways of life.